Lomustine and bevacizumab in progressive glioblastoma - Wick, Wolfgang; Bendszus, Martin; Sahm, Felix; Harting, Inga; Deimling, Andreas von; Platten, Michael (The New England journal of medicine, 2017)
The addition of bevacizumab to lomustine in patients with recurrent glioblastoma failed to increase overall survival but was associated with a small increase in progression-free survival.